Muhammad Abduh dan Pembaharuan Pendidikan Islam di Indonesia pada Era Kontemporer - Alkhadafi, Rahmad; -, Shofiyullah Muzammil (PERADA, 2025)
This research explores Muhammad Abduh's thoughts on Islamic education reform and its implications in the contemporary era. This research uses qualitative techniques based on library research. This study concludes that Abduh's renewal of thought in the field of education includes several things. First, the rejection of Taklid and various schools of thought that limit freedom of thought. Second, criticism of tendentious books should be corrected to be in harmony with rational and historical thinking. Third, renewal efforts at al-Azhar as the main center of Muslims, with the belief that if this institution is good then society will also be good, and vice versa. Fourth, the revitalization of old works to unearth the intellectual heritage of Islam in history, while following the correct views that are relevant to present-day conditions. The implications of Muhammad Abduh's thoughts on Islamic education in Indonesia in the contemporary era are very significant. The educational reforms he initiated can be a foundation for facing the challenges of an Islamic education system that is still trapped in traditional methods and less responsive to technological developments. His thoughts on the integration of religious knowledge and modern science can help Islamic education institutions in Indonesia create a curriculum that is holistic, innovative, and relevant to the needs of the global community.